Substantial twentieth-century Arctic warming caused by ozone-depleting substances - Polvani, Lorenzo M.; Previdi, Michael; England, Mark R.; Chiodo, Gabriel; id_orcid:0 000-0002-8079-6314; Smith, Karen L. (Nature Climate Change, 2020)
ISSN:1758-6798